Time to challenge the spurious hierarchy of systematic over narrative reviews? - Greenhalgh, T; Thorne, S; Malterud, K (John Wiley & Sons Ltd, 2018)
Systematic reviews are generally placed above narrative reviews in an assumed hierarchy of secondary research evidence. We argue that systematic reviews and narrative reviews serve different purposes and should be viewed as complementary. Conventional systematic reviews address narrowly focused questions; their key contribution is summarising data. Narrative reviews provide interpretation and critique; their key contribution is deepening understanding.